CBMT-08. IN VIVO EVALUATION OF PENTOSE PHOSPHATE PATHWAY ACTIVITY IN ORTHOTOPIC GLIOMA USING HYPERPOLARIZED δ-[1-13C]GLUCONOLACTONE. (11th November 2019) - Batsios, Georgios; Viswanath, Pavithra; Cao, Peng; Taglang, Celine; Subramani, Elavarasan; Flavell, Robert; Larson, Peder; Ronen, Sabrina
Abstract: The pentose phosphate pathway (PPP) generates NADPH and ribose 5-phosphate, which are involved in the scavenging of reactive oxygen species and the synthesis of nucleotides. As such, the PPP is typically upregulated in cancer cells to address the metabolic needs of rapid cell proliferation. Imaging PPP upregulation could therefore be useful in tumor assessment. One intermediate of the pathway is 6-phospho-δ-gluconolactone (6P-δ-GL), which is produced by phosphorylation of δ-gluconolactone. 6P-δ-GL is further metabolized to 6-phospho-gluconate (6PG). The goal of our study was to evaluate, for the first time, whether hyperpolarized (HP) δ-[1- 13 C]gluconolactone can be used to assess PPP flux and detect the presence of tumor in an orthotopic glioma rat model. Athymic nude rats bearing orthotropic U87 tumors or age-matched tumor-free controls were investigated. HP studies were performed following intravenous injection of HP δ-[1- 13 C]gluconolactone and metabolic images using a flyback spectral-spatial echo-planar spectroscopic imaging pulse were acquired. The data were processed using in-house Matlab code. 6P-δ-GL and 6-phospho-γ-[1- 13 C]gluconolactone were observed in all rats 10 seconds after HP δ-[1- 13 C]gluconolactone injection, followed 5 seconds later by production of 6PG observed at 179.3ppm. These data indicate that HP δ-[1- 13 C]gluconolactone likely crosses the blood-brain barrier, consistent with its transport via glucose transporters, and is rapidly metabolized. Importantly, 6PG was significantly higher in tumor voxels. The ratio of 6PG-to-6P-δ-GL was comparable in normal brain and in normal-appearing contralateral brain of tumor-bearing rats at 0.43±0.09 and 0.45±0.06 respectively (p=0.85), but significant higher in the tumor regions at 0.70±0.11 (p=0.04 and p=0.02 respectively), consistent with the elevated PPP flux that typically occurs in tumor cells. Our results indicate, to our knowledge for the first time, that metabolism of HP δ-[1- 13 C]gluconolactone can be assessed in the brain and that elevated 6PG production in glioma provides a potential metabolic imaging approach to probe tumor development, recurrence and response to therapy.